If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -5) = 4x + 7 Reorder the terms: 3(-5 + 2x) = 4x + 7 (-5 * 3 + 2x * 3) = 4x + 7 (-15 + 6x) = 4x + 7 Reorder the terms: -15 + 6x = 7 + 4x Solving -15 + 6x = 7 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -15 + 6x + -4x = 7 + 4x + -4x Combine like terms: 6x + -4x = 2x -15 + 2x = 7 + 4x + -4x Combine like terms: 4x + -4x = 0 -15 + 2x = 7 + 0 -15 + 2x = 7 Add '15' to each side of the equation. -15 + 15 + 2x = 7 + 15 Combine like terms: -15 + 15 = 0 0 + 2x = 7 + 15 2x = 7 + 15 Combine like terms: 7 + 15 = 22 2x = 22 Divide each side by '2'. x = 11 Simplifying x = 11
| 1.2z+1.152=30.6 | | 4(x-7)(x-8)(x+7)=0 | | 12+3y-8+4y= | | 0.5x+5.4=8.6 | | 0=x^2+0-67 | | -3(x-3)=21 | | 5p+24.2=28.65 | | x+1.4x=500 | | -x-9=13-3x | | 0.45x+0.6=0.6x | | 4lnx=3 | | (5x+3)=(4x-1) | | (6x)=42 | | -22+5x=-4x+32 | | 9x(-1)-7=x | | -7-5[2x-5(10+6x)]= | | -3-x=-2x+8 | | (-0.75x+6)-(2.5x-1.9)= | | 2(3x+2)=2x+1+x | | 100=v+23 | | 7-3x=-4+13 | | 29z+15z+11z+35z+46z+14z= | | (m-n-1)(m-n+1)= | | 25=5r | | x+x+2=758 | | 42=7t | | 17-x=5+6 | | 5b+4=6b-4 | | 3-6x=4x+0 | | 4(2x)=100 | | 42x-45=-72 | | 5x-1+9x=4x-7 |